SYNERGISTIC EFFECT OF AM FUNGUS AND RHIZOBIUM INOCULATION ON ARACHIS HYPOGEAE L. IN UNSTERILE SOIL - K.P. KOLKAR; H.C. LAKSHMAN; P.A.HOSAMANI (International Journal of Pharma and Bio Sciences, 2013)
Arachis hypogeae L. groundnut is a second largest source of edible vegetable oil. Medicinally the oil is used as a laxative and emollient. Arachis hypogeae L. seedlings were grown in earthen pots containing unsterilized soil inoculated with Glomus fasiculatum , Rhizobium or a combination of symbionts. After 90 days growth, plant height, dry weight, root dry weight,mycorrhizal colonization, spore number, percent of yield, nitrogen and phosphorous content were quantified. Plant with either a combination of mycorrhizal fungi and Rhizobium grew taller and produced higher dry matter of root and shoot than infected with Rhizobium species alone or control plants. The presence of Rhizobium increased the nitrogen content of above the ground. Foliage number increased with inoculation of mycorrhizal fungi and phosphorus content was increased. In the present study mycorrhizal fungi and Rhizobium were found to be synergistic with respect to nitrogen fixation and percent of root colonization.